Prevertebral thoracic abscess in neonate- a previously unknown cause of respiratory failure in neonates: a case report - Sharma, Pragya D.; Devaranavadagi, Ranganatha A.; Kannur, Netra S.; Nagesh, Karthik (International Journal of Contemporary Pediatrics, 2024)
A prevertebral abscess is one of the serious infections of the prevertebral space. Prevertebral abscess cases are reported in children and adults. However, it has not been reported in neonates to date, and our team report a case of prevertebral abscess in a 17-day-old baby. A previously healthy term neonate with no antecedent risk factors and an evident source of infection presented with respiratory failure and repeated extubation failures. On evaluation, bronchoscopy revealed antero-posterior collapse of the trachea; further evaluation by computed tomography scan revealed a prevertebral thoracic abscess which was compressing the trachea. Surgical drainage and IV antibiotics led to complete resolution, and the neonate is doing well on follow-up. Prevertebral thoracic abscess is an uncommon cause of airway compression in the neonates. It is important to consider in the differential diagnosis of airway compression.